PEREMPUAN PEGAWAI NEGERI SIPIL DALAM PERNIKAHAN POLIGINI - Siti Nursanti (Jurnal Politikom Indonesiana, 2016)
ABSTRACTThe study is titled "Women In Marriage Polygyny " This stems from the rise of polygynous marriages occur among the people of Indonesia , especially among civil servants in Khanewal district . Polygynous marriage is a form of  marriage that is undertaken by one man with several women in the same time period. Polygynous marriage is a marriage that has not been widely accepted in society. Polygynous marriage may be performed in the Islamic religion with the terms and conditions applicable. For PNS Women polygynous marriages may be performed with the  terms  must  obtain  permission  from  the  first  wife.  This  study  wants  to  examine  the  significance  of  women, marriage  and  the  meaning  of  women's  experience  of  civil  servants  communication  in  polygynous  marriages  in karawang district. The theory is used to form the framework is Symbolic Interaction theory of George Herbert Mead and  Alferd  Schutz  Theory  Phenomenology.  Researchers  using  qualitative  methods  through  a  phenomenologic approach to tradition. This tradition seeks to uncover and understand the reality of the research is based on the perspective  of  the  research  subjects.  In  this  study  using  eight  informants  as  sources  of  information.  The  results showed  that  PNS  Women  in  polygynous  marriages  bekeja  interpret  that  women  as  a  form  of  self-actualization, recognition in the community and economic independence. Polygynous marriage is a test of patience, protection and berpasangan  needs.  Communication  experiences  of  women  civil  servants  in  polygynous  marriages  as  a  form  of torture against himself and his family, the shape and strength of true happiness and a test of patience in undergoing a test of life.Keywords: WomenMarriagePolygyny, Symbolic Interaction, Phenomenology